Seneca Valley virus 3Cpro antagonizes host innate immune responses and programmed cell death - Zhang, Xin-yu; Li, Yu-ying; Huang, Hai-xin; Zhao, Chen-chen; Lei, Xiao-xiao; Zhao, Bao-peng; Lu, Jing-yi; Lan, Tian; Sun, Wen-chao (Frontiers in Microbiology, 2023)
Seneca Valley virus (SVV), a member of the Picornaviridae family, may cause serious water blister diseases in pregnant sows and acute death in newborn piglets, which have resulted in pig production and economic losses in pig production. The 3C protease is a vital enzyme for SVV maturation and is capable of regulating protein cleavage and RNA replication of the virus. Additionally, itthis protease can impede the host'shost's innate immune response by targeting the interferon pathway'spathway's principal factor and enhance virus replication by modulating the host'shost's RNA metabolism while simultaneously triggering cell-programmed cell death. This article reviews recent studies on SVV 3C functionfunctions, which includesinclude viral replication promotion, cell apoptosis modulation and host immune response evasion, and provides a theoretical basis for research on preventing and controlling SVV infection.